Functional Neuroimaging as an Assessment Tool in Critically Ill Patients. Issue 1 (3rd November 2022) - Norton, Loretta; Kazazian, Karnig; Gofton, Teneille; Debicki, Derek B.; Fernandez‐Espejo, Davinia; Peelle, Jonathan E.; Al Thenayan, Eyad; Young, G. Bryan; Owen, Adrian M.
Abstract : Objective: Little is known about residual cognitive function in the earliest stages of serious brain injury. Functional neuroimaging has yielded valuable diagnostic and prognostic information in chronic disorders of consciousness, such as the vegetative state (also termed unresponsive wakefulness syndrome). The objective of the current study was to determine if functional neuroimaging could be efficacious in the assessment of cognitive function in acute disorders of consciousness, such as coma, where decisions about the withdrawal of life‐sustaining therapies are often made. Methods: A hierarchical functional magnetic resonance imaging (fMRI) approach assessed sound perception, speech perception, language comprehension, and covert command following in 17 critically ill patients admitted to the intensive care unit (ICU). Results: Preserved auditory function was observed in 15 patients (88%), whereas 5 (29%) also had preserved higher‐order language comprehension. Notably, one patient could willfully modulate his brain activity when instructed to do so, suggesting a level of covert conscious awareness that was entirely inconsistent with his clinical diagnosis at the time of the scan. Across patients, a positive relationship was also observed between fMRI responsivity and the level of functional recovery, such that patients with the greatest functional recovery had neural responses most similar to those observed in healthy control participants. Interpretation: These results suggest that fMRI may provide important diagnostic and prognostic information beyond standard clinical assessment in acutely unresponsive patients, which may aid discussions surrounding the continuation or removal of life‐sustaining therapies during the early post‐injury period. ANN NEUROL 2023;93:131–141